"Bo on me czyny uznał za zuchwałe" - kilka słów o winie Antygony - Kotlińska-Toma, Agnieszka (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2015)
This article aims to examine Sophocles’ play from the perspective of Creon as protagonist. Antigone, contrary to later modern interpretations, is not identified as upholding eternal divine law in confrontation with the laws of the state, but is rather shown as committing hybris, which destroys her and her relatives. The interpretation of Antigone, based on the presentation of the heroine as a blameless and courageous woman, who fights alone against an indisputably legitimate matter, is spurious. This of course does not alter the fact that this play functions in European culture in precisely this and in no other way. This alternative interpretation, though erroneous, has become the basis for so many philosophical, literary and even religious discussions, that it cannot be simply discarded.
Keywords: Greek tragedy; drama; Sophocles; Antigone; Creon; Thebes